Non-Equidistant Multivariable Model MGRM (1,n) Based on Vector Valued Continued Fraction and Reciprocal Accumulated Generating Operation - Youxin Luo (Institute of Advanced Engineering and Science, 2014)
Grey system theory is a scientific theory possessed with wide adaptability to study poor information. The construction method of the background value in multivariable grey model was analyzed. The trapezoid formula and extrapolation method using rational interpolation and numerical integration was proposed based on the theory of vector valued continued fractions. And a non-equidistant multivariable grey model MGRM(1,n) was built through applying reciprocal accumulated generating operation. The model is suitable for building both equidistant and non-equidistant models, and it broadens the application range of the grey model and effectively increases both the fitting and the prediction precisions of the model. The applicability and the reliability of the model built were proven by real cases. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.2709